Using triangualtion to enhance the quality of a qualitative research investigating the oral instructional language of teacher trainees in teaching science in english - Abd. Aziz @ Ahmad, Azian; Abdul Raof, Abdul Halim (2008)
Qualitative research has for decades been prolifically used in the social sciences. It continues to thrive and has made numerous profound contributions in providing insights into the social world. Nevertheless, despite such an achievement, qualitative research has often been labelled as unscientific due to its subjective and interpretive nature. Such a negative perception is more often than not caused by some methodological factors which have distorted the results in one way or another. Thus, what is needed is to use some form of standards or guidelines which could help enhance the trustworthiness of a qualitative research as well as minimise any threats to its validity. One such guideline is the use of triangulation. Four basic types of triangulation (i.e. theoretical, data, method and investigator triangulation) are described in this paper in the context of investigating the oral instructional language of teacher trainees in teaching science in English.